Comparison of Non-albuminuric and Microalbuminuric Diabetic Patients (Medicine Today, 2025)
Introduction with Objective: The aim of the present study was to compare the Non-albuminuric and microalbuminuric Diabetic Patients. Materials and Methods: This comparative study was conducted in the Department of Laboratory Medicine, BSMMU, Shahbagh, Dhaka. The duration of the study was from June 2022 to February 2023. Diagnosed patients with diabetes mellitus who fulfill the inclusion and exclusion criteria were selected as the study population. After data collection and processing, all statistical analysis was done by SPSS software windows version 26. Result: Majority of microalbuminuric subjects (n=17, 37%) were 60-69 years. Male patients were suffering from more microalbuminuria. Mean (±SD) BMI of non-albuminuric and microalbuminuric subjects were 23.76±4.18 kg/m2 and 23.90±3.50 kg/m2 respectively. Mean(±SD) disease duration was 6.63±1.37 years in non-albuminuric and 7.41±1.73 years in microalbuminuric subjects. The difference of disease duration was statistically significant between non-albuminuric & microalbuminuric subjects (p